Rasional Emotif Behavior Therapy (REBT) Islam Dalam Menumbuhkan Sikap Mental Positif - Hany Paturrochmah (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
Islamic Rational Emotive Behavior Therapy (REBT) in Fostering Positive Mental Attitudes. This study aims to describe the Islamic REBT theory in fostering a positive mental attitude. The method used in this research uses literature study sourced from books, scientific articles, websites, and similar previous research results and can be used to get a theoretical basis for the problem to be studied. The results of the analysis explain that the implementation of the REBT theory contained in Islamic values can make individuals have healthy personalities and will make individuals have mature personalities, able to build and strengthen themselves in fostering positive mental attitudes. Because basically the body of each individual is influenced by 4 related things, namely: aql, nafs, qalb and spirit.  Keywords: Islamic REBT, Positive Mental Attitude